2016
DOI: 10.1002/ecy.1541
|View full text |Cite
|
Sign up to set email alerts
|

Warm vegetarians? Heat waves and diet shifts in tadpoles

Abstract: Temperature can play an important role in determining the feeding preferences of ectotherms. In light of the warmer temperatures arising with the current climatic changes, omnivorous ectotherms may perform diet shifts toward higher herbivory to optimize energetic intake. Such diet shifts may also occur during heat waves, which are projected to become more frequent, intense, and longer lasting in the future. Here, we investigated how heat waves of different duration affect feeding preferences in omnivorous anur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 50 publications
(102 reference statements)
1
47
1
2
Order By: Relevance
“…Likewise, grasshoppers that could perceive the presence of a predator (spider) selected an intake target higher in carbohydrates than did controls (Hawlena & Schmitz, 2010). Other studies have shown that omnivorous invertebrates increase the relative intake of plant over animal tissue at higher temperatures Carreira, Segurado, Laurila, & Rebelo, 2017;Carreira et al, 2016;Malzahn, Doerfler, & Boersma, 2016), presum-ably to obtain extra carbon to meet the increased metabolic costs for ectotherms at higher temperatures . Studies using chemically defined diets specifically showed that mealworms (Tenebrio molitor L.) (Rho & Lee, 2017) and Spodoptera litura caterpillars (Lee, Jang, Ravzanaadii, & Rho, 2015) increased their preference for carbohydrate relative to protein at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, grasshoppers that could perceive the presence of a predator (spider) selected an intake target higher in carbohydrates than did controls (Hawlena & Schmitz, 2010). Other studies have shown that omnivorous invertebrates increase the relative intake of plant over animal tissue at higher temperatures Carreira, Segurado, Laurila, & Rebelo, 2017;Carreira et al, 2016;Malzahn, Doerfler, & Boersma, 2016), presum-ably to obtain extra carbon to meet the increased metabolic costs for ectotherms at higher temperatures . Studies using chemically defined diets specifically showed that mealworms (Tenebrio molitor L.) (Rho & Lee, 2017) and Spodoptera litura caterpillars (Lee, Jang, Ravzanaadii, & Rho, 2015) increased their preference for carbohydrate relative to protein at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a better understanding of the relationship between tadpole diets and temperature becomes increasingly relevant in predicting the future structure and function of freshwater communities, which are predominantly composed of ectothermic species. Omnivorous tadpoles may adapt to increasing temperatures through the optimisation of energetic intake via a relative increase in plant matter consumption (Carreira et al, 2016). Although similar adaptations have been observed in omnivorous invertebrates (Boersma et al, 2016;Clissold, Coggan, & Simpson, 2013;Lee, Jang, Ravzanaadii, & Rho, 2015); it is less clear whether this response is likely to occur in other ectothermic omnivorous vertebrates as temperatures continue to increase.…”
Section: Stable Isotope Analysesmentioning
confidence: 92%
“…Furthermore, Arribas et al (2015) observed both P. cultripes and Pelophylax perezi feeding at a higher ratios showed support for omnivory and suggested that some degree of diet specialisation in these tadpoles was probably influenced by temperature changes. Omnivorous tadpoles may adapt to increasing temperatures through the optimisation of energetic intake via a relative increase in plant matter consumption (Carreira et al, 2016). Discoglossus galganoi, which is primarily carnivorous, became more herbivorous and assimilated a higher proportion of plant material in the spring temperature treatment of 17-21°C (which simulated temperature rising during spring).…”
Section: Stable Isotope Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). 1 The proportions of animal and plant material assimilated by tadpoles offered both diets simultaneously were estimated using stable isotopes ( 13 C/ 12 C, 15 N/ 14 N), which allow reliable and time-integrated estimates of their diets, despite not directly quantifying consumption.…”
mentioning
confidence: 99%